Microstrip Antenna Design Circular and Disc Sector Using Multilayer Parasitic Method for Gain Enhancement at 2.4 GHz Frequency - Sihombing, Euodia; Koesmarijanto, Koesmarijanto; Imammuddin, Azam Muzakhim (JURNAL JARTEL: Jurnal Jaringan Telekomunikasi, 2025)
WiFi has become a wireless communication technology device that is very important in everyday life, so the number of devices that require a stable WiFi connection is increasing. WiFi antennas also have limited gain which causes signal coverage to not be optimal and signal quality to decrease, especially in environments with many obstacles. Conventional antennas also have uneven radiation patterns and limited bandwidth which can limit performance, especially in traffic-dense environments. Therefore, a microstrip antenna is needed to increase the gain so that the range can be longer, the radiation pattern is focused in one direction and sufficient bandwidth. Microstrip antennas have the advantages of being small, cheap and light. This research discusses increasing gain using the multilayer parasitic method with 4 layers with circular patches and sector discs. Application of the working frequency used by microstrip antennas (2401-2495) MHz for WiFi (Wireless Fidelity) networks. The fabricated multilayer microstrip antenna works at a frequency of 2447 MHz, has a return loss value of -13.91 dB, VSWR 1,505 and is in the frequency range (2411 - 2507) MHz. At the 2420 frequency, the gain value is 14.95 dBi with a bandwidth of 88 MHz, while at the 2440 MHz frequency the gain is 10.5 dBi. This antenna is directional because it has effective radiation in a certain direction.